Experiential Learning Learning Strategies for Improving Student Academics in Elementary Schools - Mumtaz Mufida Syarief Ginting (International Journal of Students Education, 2024)
In the teaching and learning process, teachers have the task of choosing appropriate learning strategies/models according to the material presented. On the other hand, the existing problem is that the ongoing learning process in elementary school tends to be limited to textual and monotonous. This strategy is carried out by providing it in stages, starting with providing lecture material and questions and answers. Implementation is the basis or reference so that the process in this community service program runs systematically, structured and directed. The aim of this research is to increase teachers’ understanding in managing the classroom by using active learning strategies. This research uses a literature review research method. The content and discussion in this research is related to the implementation of learning strategy activities that have been researched on improving students’ academics, in the results and discussion of which there are active learning strategy activities for elementary school teachers so that teachers can increase their insight and experience in carrying out the learning process in the classroom actively and creative.